On the fringes of power : the life and turbulent career of Senator Stephen Wallace Dorsey - Graña, Mari, 1936- (TwoDot, 2015)
"Touted in his time as one of the 'great men of the West, ' Stephen Wallace Dorsey was a Reconstruction carpetbagger who went to Arkansas and finagled and bribed his way into getting elected to the US Senate after living only two years in the state before heading West to seek his fortune. From a fraudulent New Mexico land claim to taking up mining claims and real estate in Southern California, he used sheer cunning and guile to manipulate the system of the Gilded Age to his own ends. Dorsey was a major presence in early New Mexico--which was no-holds-barred frontier corruption--with his flair for excess. Excess is in everything he did, his manipulative 600,000-acre-land-grab, his political shenanigans, his excessive drinking, his extravagant lifestyle always on display. In his fraudulent dealings he was caught out--not by the law, but those more conniving than he was. His fantastic mansion in the middle of a still-today empty prairie in northeastern New Mexico was of state-wide historical importance before the state could no longer afford to keep it"--Publisher's website